Work Standards in Selected Third Party Logistics Operations: MTM-LOGISTICS Case Study. (2017) - Koptak, Michal; Džubáková, Martina; Vasilienė-Vasiliauskienė, Virgilija; Vasiliauskas, Aidas Vasilis
Abstract: Good relations between company, suppliers and logistics provider must be based on a win-win strategy, so quality (and price) of services is essential factor in establishing long-term relationships. In this paper we offer the MTM (Methods Time Measurement) standard development as basis for determining quality and price parameters for fair 3PL contract. We use case study and "MTM draft development" to show opportunities to increase the productivity and reduce the costs related to outsourced processes in the selected enterprise. We provide a brief overview of the methodology MTM-logistics and show MTM as a tool for optimization of logistics operations in order to create the standards of individual activities that are outsourced to external companies in selected industrial enterprise. Standardization gives us a good basis for quality improvement and price negotiation.